Mapping of pathways of care, assessment of delays and gap analysis in provision of care following road traffic injury among patients in selected tertiary hospitals in urban Karnataka, South India - Prabhu, Sudhir Haladi; Rashmi, Anusha; Kundapur, Rashmi; Sathyanath, Shreyaswi M (Indian Journal of Community Health, 2021)
Background: Evidence-based public health advocates decision making based on best available scientific evidence, hence it is important to gather evidence of current scenario of trauma care. Aim & Objective: To determine pathways of care and delays among Road Traffic Injury patients and assess gaps in resources. Settings and Design: This cross-sectional study was conducted in selected tertiary care hospitals in Mangaluru taluk, Karnataka. Methods and Material: Participants were administered validated proformas on prehospital and hospital care. WHO trauma care checklist was used for capacity assessment and gap analysis. Statistical analysis used: Time intervals are expressed as measures of central tendency and dispersion. Descriptive analysis is given as percentages and proportions. Results: Median pre-hospital time was 30 minutes. Overall, 67.5% of the patients reached within golden hour. Majority (64.1%) were directly transported to current hospital. All patients received first aid, but only 0.8% received it at the RTI site. First aid was mostly administered by doctors (68.7%) or nursing staff (31.1%) and none by bystander. Insurance coverage was 32.8% and 87.9% incurred out of pocket expenditures. Scores were low in GP level hospital. Conclusions: Although transport was within the golden hour, pre-hospital care was poor. Out of pocket expenditures were high.